The Effects of Crocin on Bone and Cartilage Diseases - Vafaei, Shayan; Wu, Xuming; Tu, Jiajie; Nematollahi-mahani, Seyed Noureddin (Frontiers in Pharmacology, 2022)
Crocin, the main biological active carotenoid of saffron, generally is derived from the dried trifid stigma of Crocus sativus L. Many studies have demonstrated that crocin has several therapeutic effects on biological systems through its anti-oxidant and anti-inflammatory properties. The wide range of crocin activities is believed to be because of its ability to anchor to many proteins, triggering some cellular pathways responsible for cell proliferation and differentiation. It has also therapeutic potentials in arthritis, osteoarthritis, rheumatoid arthritis, and articular pain probably due to its anti-inflammatory properties. Anti-apoptotic effects, as well as osteoclast inhibition effects of crocin, have suggested it as a natural substance to treat osteoporosis and degenerative disease of bone and cartilage. Different mechanisms underlying crocin effects on bone and cartilage repair have been investigated, but remain to be fully elucidated. The present review aims to undertake current knowledge on the effects of crocin on bone and cartilage degenerative diseases with an emphasis on its proliferative and differentiative properties in mesenchymal stem cells.